The Effect of Perceived Organizational Support, Psychological Empowerment and Structural Empowerment on Employee Engagement and Job Performance at PT. Angkasa Pura I (Persero) - Agus Purbo Widodo; Budiyanto; Suhermin (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to examine and determine the impact of the following factors on job performance: (1) perceived organizational support; (2) psychological empowerment; (3) structural empowerment; (4) perceived organizational support (pos); (5) psychological empowerment; (6) structural empowerment; (7) employee engagement on job performance; and (8) perceived organizational support (pos). This study is quantitative in nature. All PT. Angkasa Pura I personnel make up the study's population. The research sample was 292 people. Using the proportional random sampling method, samples from the population were taken. A google form was used to gather research data. using structural equation modeling to analyze data (SEM). All of the proposed hypotheses, with the exception of the third, are accepted as a result of this study.